Juvenal’s Global Awareness : Circulation, Connectivity, and Empire - Umurhan, Osman (Routledge Monographs in Classical Studies, 2017)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgments -- 1 Introduction: Geography, empire, and globalization -- Globalization, its theories, and second century Rome: Interconnection, time-space compression, and deterritorialization -- Interconnection -- Time-space compression and deterritorialization -- Empire and territorial space -- Consciousness and reflexivity -- Satire 1 and the coordination of location -- Juvenal's world of circulation and global awareness -- 2 Culture and globalization: Satires 1, 3, 6-7, and 9 -- To Rome all circulates -- Lucilius and the geographic construction of place -- To Rome, the hub of interconnectivity and global flows -- Global flow and deterritorialization -- Results -- 3 Food and globalization: Satires 4, 5, and 11 -- Reading globalization in objects -- Satire 4: The rhombus and a consciousness of the world at large -- Vivaria and piscinae: The local and global -- Rome's unstable periphery -- Deterritorialization and reterritorialization: Satires 5 and 11 -- 4 Globalization and the periphery: Satire 15 -- Satire 15: A prelude to cannibalism (15.1-32) -- The challenge of the chew -- Metaphoric cannibalism -- Decentering on the periphery -- Rome's increasing multiplicity -- 5 Globalization and the army's circulation of empire: Satire 16 -- Back where we began? -- History of violence: The military -- Juvenal's soldiers and the circulation of violence -- The emperor and his troops -- Juvenal's satiric salvo -- The satirist soldier to the rescue -- Felix: The insurance for military success -- Political instability from the Year of the Four Emperors to Trajan -- Trajan (98-117 ce) -- Aftermath -- 6 Epilogue: The rhizome satirist -- Rhizome -- Rhizomatic satire -- Index locorum -- General index.